Applying the Waterfall method to build applications E-Commerce at Palembang City Computer Embroidery Partners - Revina Pravita Sari; Karnadi; Jimmie (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
The role of public media such as websites is needed to disseminate products or goods, especially for small businesses that have the potential to face competition with other businesses. Websites are an alternative solution to the limitations of the business area and provide the speed of bidding and provide the opportunity to become the best seller. E-Commerce makes consumers more time-saving, and differentiates cheaper prices, it provides various things to sell and minimizes crowding in stores, E-Commerce Websites support our trade business by providing products and services online to users in various regions. Websites are an alternative solution to the limitations of the business area and provide the speed of bidding and provide the opportunity to become the best seller. The researcher found a problem that the border computer partner figure in data processing is still done manually with paper media. Therefore, the author took the initiative to design an E-Commerce information system for Computer Embroidery Partners in Palembang City with a waterfall method design. This waterfall method has a fairly clear workflow, measurable work time and clear documentation. This research was tested with the Blackbox test, with this website it is hoped that it can facilitate the sales system for Computer Embroidery Partners in making sales reports automatically and with this website it is hoped that it can be a promotional medium for Computer Embroidery Partners